The wedding contract : a Balinese love story - Dawkins, David; David Dawkins Productions (Firm); FeelSales (Firm) ([United States] : David Dawkins Productions, 2014)
When a Balinese girl is denied permission to marry outside of her clan, there is a traditional solution for the family of the suitor: 1. Draw up a Wedding Contract. 2. Kidnap the Bride.--
Originally released as a motion picture in 2014.
Cinematographer and editor, David Dawkins.
In Balinese and English with English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed September 27, 2019)
Keywords: Dawkins, David; Marriage customs and rites -- Indonesia -- Bali Island; Weddings -- Indonesia -- Bali Island; Bali Island (Indonesia) -- Social life and customs; Documentary films; Nonfiction films; Feature films; Internet videos; Streaming video